Copper-catalyzed synthesis of 3-allyl-2-aminoindoles from 3-diazoindolin-2-imines and allyltrimethylsilane. Issue 12 (22nd March 2019) - Lang, Bo; Zhou, Yuxuan; Lu, Ping; Wang, Yanguang
Abstract: A novel and facile approach to 3-allyl-2-aminoindoles via the copper-catalyzed reaction of 3-diazoindolin-2-imines with allyltrimethylsilane is described. The domino reaction proceeds efficiently in one-pot and shows broad substrate scope with respect to the diazo substrates. Furthermore, the synthesized 3-allyl-2-aminoindoles can be conveniently transformed into 3-allyl-3-hydroxylindolin-2-imines and 3-allyl-3-fluoroindolin-2-imines. Graphical abstract: Image 1